ANALISIS KEBUTUHAN MASYARAKAT BERKAITAN DELAPAN PILAR PENGABDIAN MASYARAKAT DI KAMPUNG SANGSANG KECAMATAN SILUQ NGURAI - Situmorang, Roni Marudut; Santoso, Hendra (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2024)
Abstract. This study aims to analyze the community needs in Sangsang Village based on the eight pillars of community service: education, health, income, economic independence, socio-culture, environmental participation, community institutions, and infrastructure. The research employs a descriptive quantitative and qualitative approach, with data collected through social mapping surveys, public consultations, questionnaires, and field observations. Respondents were selected using purposive sampling. Data analysis was conducted descriptively to provide a comprehensive overview of community needs, validated through data triangulation. The findings reveal that Sangsang Village, located in Siluq Ngurai Subdistrict, has a population of 395 people, predominantly of productive age (15–54 years). The education level is relatively low, with most residents not completing primary school or lacking formal education. Educational infrastructure is limited to early childhood education (PAUD) and elementary schools (SD). Furthermore, the poverty index reaches 34%, with 31 out of 120 households categorized as pre-prosperous. Community needs analysis was developed based on social mapping and public consultation, prioritizing programs to strengthen education and build tourism-supporting infrastructure. The results of this analysis are expected to serve as a strategic foundation for planning relevant, effective, and comprehensive development programs aligned with the eight pillars of community service. Keyword: Comumunity Development; Need Analysis; Social Mapping. Abstrak. Penelitian ini bertujuan menganalisis kebutuhan masyarakat di Kampung Sangsang berdasarkan delapan pilar pengabdian masyarakat, yaitu pendidikan, kesehatan, pendapatan, kemandirian ekonomi, sosial budaya, partisipasi lingkungan, kelembagaan komunitas, dan infrastruktur. Metode penelitian menggunakan pendekatan kuantitaif dan kualitatif deskriptif dengan teknik pengumpulan data melalui survei pemetaan sosial, konsultasi public, pengisian kuesioner dan observasi lapangan. Responden dipilih menggunakan purposive sampling. Analisis data dilakukan secara deskriptif untuk memberikan gambaran komprehensif kebutuhan masyarakat, yang divalidasi melalui triangulasi data. Hasil penelitian menunjukkan bahwa Kampung Sangsang, yang terletak di Kecamatan Siluq Ngurai, memiliki jumlah penduduk 395 jiwa dengan dominasi usia produktif (15–54 tahun). Tingkat pendidikan masyarakat masih rendah, dengan sebagian besar belum tamat SD atau tidak bersekolah. Infrastruktur pendidikan di Kampung Sangsang terbatas pada PAUD dan SD. Selain itu, indeks kemiskinan mencapai 34%, dengan 31 dari 120 kepala keluarga tergolong pra-sejahtera. Analisis kebutuhan masyarakat disusun berdasarkan pemetaan sosial dan konsultasi publik, dengan prioritas program pada penguatan pendidikan dan pembangunan infrastruktur pendukung pariwisata. Hasil analisis ini diharapkan menjadi dasar strategis bagi perencanaan program pembangunan yang relevan, efektif, dan menyeluruh, sesuai delapan pilar pengabdian masyarakat. Kata Kunci: Pengembangan Masyarakat; Analisis Kebutuhan; Pemetaan Sosial.